2018
DOI: 10.1007/s12237-018-0369-8
|View full text |Cite
|
Sign up to set email alerts
|

Annual Phytoplankton Primary Production Estimation in a Temperate Estuary by Coupling PAM and Carbon Incorporation Methods

Abstract: Phytoplankton primary production varies considerably with environmental parameters especially in dynamic ecosystems like estuaries. The aim of this study was to investigate short-term primary production along the salinity gradient of a temperate estuary over the course of 1 year. The combination of carbon incorporation and fluorescence methods enabled primary production estimation at short spatial and temporal scales. The electron requirement for carbon fixation was investigated in relation with physical-chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 89 publications
2
12
0
Order By: Relevance
“…The Surprising high values recorded in winter were attributed rather to freshwater chlorophyll detrital matter than living phytoplankton (Morelle et al 2018).…”
Section: Dynamics Of the Size Fractionated Phytoplankton Biomassmentioning
confidence: 85%
See 2 more Smart Citations
“…The Surprising high values recorded in winter were attributed rather to freshwater chlorophyll detrital matter than living phytoplankton (Morelle et al 2018).…”
Section: Dynamics Of the Size Fractionated Phytoplankton Biomassmentioning
confidence: 85%
“…In these conditions, the mean sampling depth at the WSI is 13.2 ± 1.4 meters. The physical-chemical parameters are described and interpreted in a previous paper (Morelle et al 2018) and a slight summary of their dynamics is given in this paper.…”
Section: Sampling Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Many regional studies have shown that Φ e,C in natural communities correlates with environmental factors such as macro-and micronutrients, temperature, salinity, light intensity, water transparency, and chl a (Lawrenz et al 2013, Schuback et al 2017, Morelle et al 2018. Mostly these relationships are empirical rather than mechanistic.…”
Section: Relationship Between φ Ec and Environmental Variablesmentioning
confidence: 99%
“…The main principle of these methods is to follow the change in the quantum yield of chlorophyll fluorescence and to derive photosynthetic parameters related to the activities of photosystem II (PSII; Kolber et al 1998). Pulse amplitude modulation and fast repetition rate fluorometry (FRRF) are among the commonly used fluorometric methods to estimate photosynthetic parameters and gross primary production in lakes and oceans (Suggett et al 2001, Melrose et al 2006, Morelle et al 2018. Fluorometric methods for determining primary production are non-intrusive, instantaneous, and sensitive, and they can measure the fluorescence variables in real time (Kolber et al 1998).…”
Section: Introductionmentioning
confidence: 99%